Reinventing Poverty Alleviation Strategies Through Corporate Social Responsibilities - Arli, Denni I.; Morrison, Pamela D.; Razzaque, Mohammed A. (ANIMA Indonesian Psychological Journal, 2008)
Poverty is one of the biggest problems facing our society today. To date, most of the re- sponse to this has been by non-profits or NGO’s, but more recently academics and a few business or- ganisations have become aware of the so called ‘bottom of the pyramid’ market and how by address- ing this market, the poorest may be able to be helped as well as there being a benefit to the company. In this paper we analyse poverty alleviation programs launched by corporations and propose an em- pirical study as a way to identify successful poverty alleviation strategies more systematically and ef- fectively. Kemiskinan adalah masalah terbesar yang dihadapi masyarakat kita saat ini. Selama ini yang tanggap terhadap masalah ini adalah lembaga nirlaba atau LSM, namun akhir-akhir ini para akademisi dan beberapa organisasi bisnis mulai menyadari apa yang dikenal sebagai pasar “dasar pi- ramida” dan bagaimana memanfaatkan pasar tersebut, yang paling miskin dapat dibantu seiring diperolehnya keuntungan bagi perusahaan. Dalam tulisan ini kami manganalisis program-program pengurangan kemiskinan yang dilancarkan oleh korporasi dan mengusulkan studi empiris sebagai jalan mengidentifikasi strategi penanggulangan kemiskinan yang berhasil dengan lebih sistematis dan efektif.